Voluntary wheel running: patterns and physiological effects in mice - Manzanares, G. (Braz J Med Biol Res, 2018)
Exercise can prevent and improve the pathophysiology of diseases and promote healthy aging. Thus, understanding the mechanisms that regulate the beneficial effects of exercise may lead to the development of new strategies to enhance quality of life and to counteract chronic diseases. Voluntary wheel running is an interesting model to study the effects of exercise in mice. Compared to forced treadmill exercise, voluntary wheel running presents several advantages such as: 1) running pattern is similar to natural running behavior of mice; 2) it is performed under non-stressed conditions, according to the rhythmicity of the animal; 3) it does not require direct interference from the researcher, and can be easily applied in long-term studies. Mice run spontaneously when given access to running wheels, for a total distance of ∼4 to 20 km per day and a total activity time of ∼3 to 7 hours a day. Hence, voluntary wheel running can result in robust endurance-like adaptation in skeletal and cardiac muscles and protect from sarcopenia. However, due to the lack of control over exercise parameters in voluntary exercise models, it is important for the researcher to understand the patterns and variability of wheel running in mice, as well as the factors that can affect voluntary running activity. Overall, voluntary wheel running in mice is a very interesting approach to study the chronic adaptation to exercise, analyze the effects of exercise, and test exercise capacity in different experimental models.